Kidney allograft rejection is associated with an imbalance of B cells, regulatory T cells and differentiated CD28-CD8+ T cells: analysis of a cohort of 1095 graft biopsies - Mai, Hoa Le; Degauque, Nicolas; Lorent, Marine; Rimbert, Marie; Renaudin, Karine; Danger, Richard; Kerleau, Clarisse; Tilly, Gaelle; Vivet, Anaïs; Le Bot, Sabine; Delbos, Florent; Walencik, Alexandre; et al. (Frontiers in Immunology, 2023)
Introduction The human immune system contains cells with either effector/memory or regulatory functions. Besides the well-established CD4+CD25hiCD127lo regulatory T cells (Tregs), we and others have shown that B cells can also have regulatory functions since their frequency and number are increased in kidney graft tolerance and B cell depletion as induction therapy may lead to acute rejection. On the other hand, we have shown that CD28-CD8+ T cells represent a subpopulation with potent effector/memory functions. In the current study, we tested the hypothesis that kidney allograft rejection may be linked to an imbalance of effector/memory and regulatory immune cells. Methods Based on a large cohort of more than 1000 kidney graft biopsies with concomitant peripheral blood lymphocyte phenotyping, we investigated the association between kidney graft rejection and the percentage and absolute number of circulating B cells, Tregs, as well as the ratio of B cells to CD28-CD8+ T cells and the ratio of CD28-CD8+ T cells to Tregs. Kidney graft biopsies were interpreted according to the Banff classification and divided into 5 biopsies groups: 1) normal/subnormal, 2) interstitial fibrosis and tubular atrophy grade 2/3 (IFTA), 3) antibody-mediated rejection (ABMR), 4) T cell mediated-rejection (TCMR), and 5) borderline rejection. We compared group 1 with the other groups as well as with a combined group 3, 4, and 5 (rejection of all types) using multivariable linear mixed models. Results and discussion We found that compared to normal/subnormal biopsies, rejection of all types was marginally associated with a decrease in the percentage of circulating B cells (p=0.06) and significantly associated with an increase in the ratio of CD28-CD8+ T cells to Tregs (p=0.01). Moreover, ABMR, TCMR (p=0.007), and rejection of all types (p=0.0003) were significantly associated with a decrease in the ratio of B cells to CD28-CD8+ T cells compared to normal/subnormal biopsies. Taken together, our results show that kidney allograft rejection is associated with an imbalance between immune cells with effector/memory functions and those with regulatory properties.